Social Media Introduction and Individual Empowerment Opportunities: Measuring Awareness among Residents of Four Cities in Nigeria - Udo Usiere, Akpan; Udo , Brightfortune (Social Empowerment Journal, 2025)
This work was on the social media introduction and individual empowerment opportunities. It was on the measuring of awareness among residents of four cities in Nigeria. The three main objectives were: To find out the proportion of persons who adapt to the introduction of social media for empowerment opportunities in four cities of Nigeria; To find out the aspect of social empowerment opportunities in which social media introduction has offered to residents of four cities in Nigeria; To find out the main barrier which affect social media contribution to raise empowerment opportunities in four cities of Nigeria. The scope of work was limited to four cities in Nigeria which were Ilorin, Onitsha, Zaria and Jos. The population was taken at 4,877,153 persons and a sample of 800. The instrument of research was a structure questionnaire proportionately distributed to respondents in the four cities. The method of research was through the use of online surveys. The data analysis was through frequency tables with percentages. Findings revealed that 488 persons supported that entertainment was the major aspect of social empowerment gained from social media against health care information, education and politics. Other findings had it that on the barriers of social media to the contributions on empowerment of users, Falsehood had 488 or (61%). This is the most significant barrier identified, accounting for more than half (61%) of the total responses. It suggests a major trust deficit in the content of radio broadcasting or adult education messaging. Individuals possibly perceive social media content as inaccurate, misleading, or propagandistic. The data highlights that content credibility, audience literacy, and socioeconomic/cultural factors play major roles in the effectiveness of radio broadcasting and adult education. The findings was also that social media restricted access due to false contents affect empowerment in as much as cost which should be considered by subsidization or free access models while programs should be culturally sensitive and, where appropriate, involve religious leaders or integrate educational content in religious programming formats. Sensitization campaigns can also address misconceptions caused by religious biases. Recommendations are that addressing these barriers through targeted strategies will enhance outreach and impact, especially in the Nigerian context where radio remains a vital tool for mass communication and education. The conclusions had it that there is a clear need for digital literacy programs, affordable internet access, and awareness campaigns that educate users about the productive use of social media—especially in underrepresented or underserved communities. There is also a need for audience feedback mechanisms and verification of facts to counteract misinformation.